Os instrumentos de registro do trabalho pedagógico e a avaliação da aprendizagem: o papel do coordenador pedagógico - Machado, Karina (Universidade Federal de São Carlos, 2021)
This qualitative research, based on a case study, started with the objective of verifying the attributions of pedagogical coordination function and its collaboration in teacher education. It also aimed to verify the perspective and the knowledge of the collaborating group; to identify, understand, and discuss the actions used by the coordinators with their teaching group; to characterize the formation of the professionals who work in this function and describe their formative path. In addition, we also aimed to learn about the actions taken based on the results of Basic Education Evaluation System (Saeb). Three coordinators for 4 and 5 years old education and four coordinators of Elementary School (1st to 5th grade) of the municipal public school of a small town in São Paulo State attended the research. To achieve the objectives, we used three data collection tools: a questionnaire, a narrative, and an interview. A fourth instrument - the visits - emerged in the Early Childhood Education coordination group, replacing the narrative. As a theoretical reference, we used the studies of Alarcão (2011) and Imbernón (2009; 2010; 2011) in the reflections on teacher training; Reis (2011) in class observation and Zabalza (2007) in the class diaries. In evaluation, we worked with the ideas of Hoffmann (2014; 2018), Depresbiteris and Tavares (2009), Zabala (2010), Luckesi (2011), Libâneo (2004; 2013) and Villas Boas (2011; 2012). Throughout the analysis and data construction, we found that the professionals perform several tasks that cover different school departments and that there is an understanding that the work emphasis should be in monitoring the pedagogical work, which ends up being reduced by the number of tasks performed. By monitoring the teaching work, the professionals use a number of strategies and, in this research, we highlight classes observation and the class records. Since the coordinator is a school professional who contributes to the continual teachers training, we propose a deepening in the use of the instruments already used, from the perspective of development the reflective teacher. In relation to the results of the external evaluation, the mock tests appear as one of the actions taken in an attempt to verify the level of student learning and the retaking of unlearned content. We propose a different look at this action, so that the evaluation is done from the perspective of monitoring the teaching and learning processes, articulated with the class records and with class observation. Therefore, we have narrowed our view to the evaluation of learning that takes place in the classroom environment, which must provide, building on and be present in the pedagogical actions, preceding and overriding any external evaluation result. The records in the instruments mentioned above, along with the evaluation process, contribute to student learning and to development of reflective and investigative professional of its practice. These instruments also contribute to the coordinator in the analysis of the pedagogical practice, from a formative perspective. We believe that a formative pedagogical positioning - both from the teacher in the classroom and as from the pedagogical coordinator actions – joined with reflective records made by teachers, will contribute to the teaching process and to the learning process.
The instruments for recording pedagogical work and evaluating learning: the pedagogical coordinator's role
Keywords: Diário de bordo; Professor reflexivo; Instrumento de avaliação; Formação continuada; Coordenador pedagógico; Class records; Reflective teacher; Evaluation instrument; Continuing education; Pedagogical coordinator; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL